45 and Up COVID Insights: a dynamic and collaborative approach to evidence-making during the COVID-19 pandemic - Greer Dawson; Kerrin Bleicher; Sarah Baynes |; Catherine D'Este; Julia Steinberg; Marianne F Weber; Jill Newby; Ding Ding; Bette Liu; Barry Edwards; Andrew Milat |; Martin McNamara (Sax Institute, 2022)
Objectives: In response to the coronavirus 2019 (COVID-19) pandemic, a research project was developed with a cohort of 45 and Up Study participants to generate timely, relevant evidence to guide policy, practice and planning. This paper describes the research model, the cohort establishment and characteristics, and some findings. Methods: A subgroup of 45 and Up Study participants was invited to enrol in 45 and Up COVID Insights -a series of five online surveys conducted during 2020-22. The model involved a close collaborative partnership with the New South Wales Ministry of Health and a panel of scientific advisers, an agile data collection methodology and rapid dissemination of findings. Frequent, iterative engagement with stakeholders provided a framework for identifying survey themes and questions and ensured wide dissemination of findings. Themes included healthcare use, attitudes toward and uptake of COVID-19 prevention measures, and the impact of the pandemic on mental health, loneliness, and lifestyle behaviours. Results: 45 and Up COVID Insights achieved strong stakeholder engagement through extensive consultation and rapid reporting of results. The project recruited a diverse cohort of 32 115 participants: median age 68 years (range: 56-100+); 8% from outer regional/remote areas; 12% from the most socioeconomically disadvantaged communities; and 9% from culturally and linguistically diverse backgrounds. The first four surveys found that the impact of the pandemic varied across populations and stages of the pandemic. Between February-April (survey 2) 2021, 10% reported missed healthcare in the past month because of the pandemic, rising to 26% by September-November 2021 (survey 4). Quality of life remained high (>90% good-excellent across the surveys). As the pandemic progressed, the proportion reporting worsened mental health as a result increased from 29% (July-December 2020, survey 1) to 46% (survey 4). In survey 2 (February-April 2021), 89% intended to get the COVID-19 vaccine, with 8% unsure. By late 2021, vaccination uptake was high, with 98% of respondents having received at least one vaccination. Conclusion: There is great value in harnessing a large longitudinal, well-described, and diverse cohort study to generate evidence in a changing context with evolving information needs. The collaborative model enhanced the value and relevance of the data to inform decisions.